PENGARUH PENERAPAN PRINSIP AKUNTABILITAS DAN TRANSPARANSI KEUANGAN TERHADAP KINERJA PENYUSUNAN ANGGARAN PADA PEMERINTAH KABUPATEN BIREUEN - Ak, Asrida (JURNAL KEBANGSAAN, 2012)
This study aims to obtain the empirical evidence of implementation of accountability and financial transparency principles which affect performance of budget arrangement in the District of Bireuen Government. Research has been conducted on all the institutions / government agencies in Bireuen District, with the multiple regression method. Sample selection is done by using the method of purposively sampling which is analyzed with the qualitative and quantitative descriptive method. Results of research indicate that implementation of the accountability and transparency have not affected the performance of the government budget in the Bireuen District. The better implementation both accountability and transparency principles, the is not better performance of the budget on the government. Partially, the principle of accountability has only influenced over the performance budget. Laws and government policies have created the government apparatus in the region must have prepared a budget plan for each job correctly and responsibly. Some obstacles that have been founded that there were respondents with less due to old patterns which not socialized. Permendagri Number 13 in 2006 and completion of Permendagri number 59 in 2007. The local government has not taken some attentions to performance indicators both at the time of budget arrangement and realization of budget to the community. In addition, providing the government accounting system and financial accounting local have been considered weakly.